2023
DOI: 10.1007/s12035-023-03437-1
|View full text |Cite
|
Sign up to set email alerts
|

Repressor Element-1 Binding Transcription Factor (REST) as a Possible Epigenetic Regulator of Neurodegeneration and MicroRNA-Based Therapeutic Strategies

Abstract: Neurodegenerative disorders (NDD) have grabbed significant scientific consideration due to their fast increase in prevalence worldwide. The specific pathophysiology of the disease and the amazing changes in the brain that take place as it advances are still the top issues of contemporary research. Transcription factors play a decisive role in integrating various signal transduction pathways to ensure homeostasis. Disruptions in the regulation of transcription can result in various pathologies, including NDD. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 167 publications
0
2
0
Order By: Relevance
“…138 response. [143][144][145] By contrast, we found that there are only a few research reports on the involvement of miRNAs in the differentiation and maturation of OLs in AD. 146,147 How miRNAs regulate factors of OLs differentiation and maturation in AD is worth further exploration.…”
Section: Future Per S Pec Tive Smentioning
confidence: 97%
“…138 response. [143][144][145] By contrast, we found that there are only a few research reports on the involvement of miRNAs in the differentiation and maturation of OLs in AD. 146,147 How miRNAs regulate factors of OLs differentiation and maturation in AD is worth further exploration.…”
Section: Future Per S Pec Tive Smentioning
confidence: 97%
“…Looking into the cellular level changes in an AD brain, various molecular pathways and intracellular signaling are dysregulated, which include Aβ and tau, inflammatory-immune responses, homeostasis and plasticity of synapses, and oxidative stress and their dysregulation results from genetic, environmental, and biologic interventions [ 17 , 18 ]. Furthermore, accumulating evidence has been pointing towards the possibility of an imbalance in epigenetic mechanisms responsible for abnormal synaptic plasticity and memory-associated genes in AD [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%